Fintech Disruption in Traditional Banking: A Bibliometric Review - Judijanto, Loso (The Es Economics and Entrepreneurship, 2025)
This study presents a comprehensive bibliometric analysis of scholarly literature on the disruption of traditional banking by financial technology (FinTech). Drawing on Scopus-indexed publications from 2010 to 2024, the study maps the intellectual structure, thematic evolution, and collaborative networks within the field. The findings reveal an exponential growth in research output, particularly post-2020, driven by accelerated digital transformation and the impacts of the COVID-19 pandemic. Major contributing countries include China, India, and the United States, with significant emerging contributions from Indonesia and other Asian economies. Keyword co-occurrence analysis identifies five major thematic clusters, including digital transformation, regulatory innovation, artificial intelligence, financial inclusion, and sustainability. Co-authorship and country collaboration maps highlight the growing interconnectedness of global research, with distinct scholarly communities in both Western and emerging markets. The study underscores the importance of interdisciplinary approaches and identifies future research opportunities in underexplored areas such as ecosystem development, platformization, and ethical FinTech.